Analisis Penegakan Hukum Pidana dalam Menangani Ujaran Kebencian Berbasis SARA di Platform Media Sosial - Deni Arianto; Anis Rindiani; Sri Yuliana (Legal Standing : Jurnal Ilmu Hukum, 2026)
This research examines the application of legal provisions related to religious-based hate speech in social media, focusing on the provocation cases that occurred during Pope visit to Indonesia in September 2024. The case involved the arrest of seven individuals, including a civil servant, suspected of making provocations such as bomb threats and church burning incitements on various social media platforms. Using a juridical-empirical approach, this research analyzes the application of the Electronic Information and Transaction Law, Anti-Terrorism Law, and related regulations in the law enforcement process. Data collection methods included interviews with law enforcement officials, legal document analysis, and case studies. The findings reveal that while Indonesia's legal framework is relatively comprehensive in regulating hate speech, its implementation still faces challenges related to the interpretation of free speech boundaries, coordination among law enforcement agencies, and technical capacity in cybercrime investigations. This research recommends strengthening law enforcement capacity, enhancing digital literacy among citizens, and harmonizing regulations regarding hate speech and online extremism to create more effective law enforcement while respecting human rights principles.